The relationship between world and African emerging economies: Trade and FDI perspectives - Aman, Abdulkadir Wahab (My University, 2018)
This study investigates the key determinants of trade and FDI positions between African emerging economies (AEE) and the world major emerging economies (WEE) by using the gravity model. The main objective is to identify the core macroeconomic and socio-cultural factors of bilateral trade and FDI between both sides. Besides, the study investigates the intra-industry trade to further intricate the type and nature of their bilateral trade. The WEE are those which are commonly recognized by all rating institutions and the AEE are identified by developing an index consisting of various criteria. Importer and exporter-fixed effect is used in order to efficiently test the impact of many dummy variables. The results illustrate that factors of trade and FDI are diversified. But, generally, the core form of the GM – GDP and distance – explains the bilateral trade and FDI positions. In the bilateral trade model, minerals production rather than petroleum production affects the level of bilateral trade. Moreover, sharing a common religion and a common language has a positive impact whereas ODA size, economic freedom, and overall trade volume are not statistically significant. Furthermore, more corrupted AEE have higher bilateral trade with some WEE than less corrupted AEE. In the FDI model, to some extent, both petrol and mineral production attracts FDI from the WEE. In addition, countries sharing similar language and religion have higher FDI positions than the others whereas higher per capita income is positively linked with FDI positions. Furthermore, AEE which signed investment agreements are hosting more FDI positions of the WEE. Additionally, the linkage between FDI positions and bilateral trade is detected. However, trade has a stronger impact on FDI than FDI’s impact on trade.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2018
Keywords: Afrika gelişen ekonomileri; İkili ticaret; DYY; Yerçekimi modeli; Endüstri-içi ticaret; African emerging economies; Bilateral trade; FDI; Gravity model; IIT